Analisis Pemanfaatan Video Animasi sebagai Media untuk Pembelajaran IPS Keberagaman Budaya di Kelas IV SD - Herman, Annisa Salisa; Azkiya, Azmi Sayyidul; Wahyuningsih, Yona (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the utilization of animated videos as a learning medium in social studies instruction on cultural diversity for fourth-grade elementary school students. The research is motivated by the predominance of conventional teaching methods that tend to reduce student engagement and enthusiasm. Using a literature review method, this study examines national scientific articles sourced from Google Scholar, academic journals, and other relevant documents. Data were analyzed through qualitative content analysis to identify patterns, similarities, and differences in findings related to learning motivation, conceptual understanding, and learning outcomes. The results indicate that animated videos positively influence students’ motivation, conceptual comprehension, and learning performance. This medium facilitates teachers in explaining abstract concepts of Indonesia’s cultural diversity in an engaging and communicative manner. However, challenges such as limited resources and teachers’ skills in developing or selecting appropriate animated materials remain. Overall, animated videos are proven to be effective in fostering active, enjoyable, and meaningful learning experiences in elementary social studies classrooms